Picture-vocab: Self-made picture dictionary to improve pupils’ vocabulary retention in Malaysia - Mohd Syaubari Othman; Hasrul Hosshan; Mohd Ridhuan Mohd Jamil; Yuvabarte Arun; Mohd Afifi Bahuruddin Setambah; Mazarul Hasan Mohamad Hanapi; Tajul Rosli Shuib; Abdul Talib Mohamad Hashim; Mohd Muslim Md Zalli (International Journal of Evaluation and Research in Education (IJERE), 2022)
This project was conducted to investigate whether the use of pictures able to improve pupils’ vocabulary retention. There were 36 pupils from an urban school located in Malaysia who are in year 4 involved as participants. The pupils were of average proficiency level of the English Language. A pre-test and post-test were conducted in order to identify the effectiveness of the intervention. An interview was carried out with 10 pupils in the post intervention for triangulation purpose. The scores from the pre-test and post-test were compared to measure the effectiveness of the intervention. Whereas, the analysis of the interview was procured on pupils’ perception towards the intervention. The findings indicate that pupils are able to remember the vocabularies taught for a longer period of time when the words are associated with pictures. Findings also indicate the use of the pictures in improving their vocabulary retention.